PROTES SOSIAL DI KAPAL PERANG: Pemberontakan Marinir Bumiputera di Kapal De Zeven Provincien 1933 - Danil Mahmud Chaniago; Umi Rusmiani Umairah (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
In the early 1930s the world community was hit by a very severe economic crisis. History records this period as the Maleise Age, namely the dramatic decline in the economic level of the world community. However, at this time precisely the Indonesian independence movement could increase its resistance to the Dutch East Indies government. This very precarious situation prompted de Jonge, the Governor-General, to save government spending and tightly restrict the national movement of the bumiputera (read: Indonesia). Not a few movement figures were later arrested and exiled without going through a court process. In turn, this economic and social crunch pushed the earth's marines on the battleship De Zeven Provincien to carry out a rebellion while singing the song Indonesia Raya. The government's injustice in terms of salary reduction is the main trigger for the emergence of social protest. The government discretion is seen by the maritime marines as an act of harassing their national values. Although this rebellion can be overcome, however, this event shows the high spirit of unity among the marines of the Bumiputera. This spirit is a reflection of the rise of national consciousness of the bumiputera, especially among marines.